BRYOZOANS ASSOCIATED WITH GASTROPOD SHELLS IN THE EARLY MIOCENE OF PATAGONIA (ARGENTINA) (Ameghiniana, 2022)
This study describes two new species of cheilostome bryozoans associated with gastropod shells from the Monte León Formation (Burdigalian, early Miocene), Argentine Patagonia. Burdwoodipora griffini sp. nov. is the second known species and the first fossil representative of the genus, whose geographic distribution is so far restricted to the Magellan region in the southern Southwest Atlantic. It differs from the type species, B. paguricola, in lacking suboral adventitious avicularia in most autozooids. Odontoporella miocenica sp. nov. is morphologically very close to the type species, the Recent O. adpressa, from which it differs in having smaller zooids with fewer areolae and relatively wider orifices. The stratigraphic range of Odontoporella is here extended from the Pleistocene to the early Miocene. Its geographic distribution includes southern South America, New Zealand, and New Caledonia, suggesting an austral origin of the genus in the Paleogene of former Gondwana. The possible association of these two species with paguroid crabs is discussed.